Exploring groundwater depletion and land subsidence dynamics in Taiwan’s Choushui river alluvial fan: insights from integrated GNSS and hydrogeological data analysis - Hung, Wei-Chia; Hwang, Cheinway; Lin, Shao-Hung; Wang, Chuan-Sheng; Chen, Yi-An; Tsai, Pei-Ching; Lin, Kuan-Chung (Frontiers in Earth Science, 2024)
This study aims to analyze the Choushui River Alluvial Fan (CRAF) in Taiwan by integrating hydrogeological data from 233 groundwater monitoring stations in four aquifers (CRAF Groundwater_NET) and 50 continuous GNSS stations (CRAF GNSS_NET). We developed an automated processing flow for GNSS static surveying within CRAF GNSS_NET, and further employed a time-series fitting method to examine the long-term trends and annual changes for both GNSS and groundwater level data. Our analysis of the time-series data from the past decade identifies areas of significant groundwater level depletion and subsidence hotspots. We explore the relationship between groundwater level variations and surface displacements within CRAF, utilizing GNSS data to analyze horizontal and vertical displacement trends, as well as annual changes. We integrate these findings with hydrogeological data to understand regional subsidence patterns. Our results indicate that CRAF is characterized by distinct hydrogeological features. The area south of the old Huwei Creek contains high-compressibility soil, making it more susceptible to subsidence under past over-extraction of groundwater. We observed a strong correlation between surface deformation and groundwater level fluctuations. The amplitudes of annual change in both groundwater level and vertical displacement increase from northeast to southwest, with the old Huwei Creek serving as a significant demarcation. The region between the 78 Expressway and Puzi Creek shows significant groundwater level decline, with the highest rate reaching 0.54 m/year. The GNSS analysis also shows a pronounced decline trend in this area, with subsidence rates between 4.2 and 5.2 cm/yr. The results of this study can form the basis for the development of appropriate groundwater management strategies for the sustainable use of groundwater resources and mitigation measures in CRAF.